1979
DOI: 10.1104/pp.63.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Structure and Function of Mitochondrial Membranes of Artichoke Tubers

Abstract: The temperature limits of the order-disorder transition, and the Arrhenius activation energy of succinate oxidase activity for mitochondria of Jerusalem artichoke (Heianthus tuberosus L.) tubers were determined from the initiation to the termination of dormancy. The temperature limits for the transition at the initiation of dormancy were 25 and 3 C. These changed to 9 and -5 C at mid-dormancy and returned to 25 and 2 C at the termination of dormancy. The Arrhenius activation energy measured in the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…If acclimation to freezing stress is viewed as the development of tolerance to these lethal barriers, it is unlikely that it would be the same barrier in all plants and, therefore, the acclimation process might not be the same for all plants and tissues. Hence, an increase in membrane fluidity, while apparently an essential feature of the acclimation process in some plant tissues, such as artichoke tubers (3) and oleander leaves (17), might not be involved in the hardening of other plants, such as winter cereals.…”
Section: Resultsmentioning
confidence: 99%
“…If acclimation to freezing stress is viewed as the development of tolerance to these lethal barriers, it is unlikely that it would be the same barrier in all plants and, therefore, the acclimation process might not be the same for all plants and tissues. Hence, an increase in membrane fluidity, while apparently an essential feature of the acclimation process in some plant tissues, such as artichoke tubers (3) and oleander leaves (17), might not be involved in the hardening of other plants, such as winter cereals.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of ultrastructural alterations in relation to frost hardiness in plants are limited (3,9,20,24). The observations of chloroplasts (26) and mitochondria (3) during cold acclimation treatments indicate some structural alterations in these organelles which may relate to plant adaptability to a given environment.…”
mentioning
confidence: 99%
“…In studies on adaptations of plant cells to low temperatures, it has been reported that the mitochondrial membrane lipid composition changes with temperature, which might serve to maintain membrane fluidity (4,7,9).…”
Section: Discussionmentioning
confidence: 99%